Advokat dan Hukum Ekonomi di Indonesia (TAWAZUN: Journal of Sharia Economic Law, 2018)
The role of law graduates in Indonesia is very important in overcoming problems that exist in society when working as an advocate. But sometimes the profession sometimes gets a slanted view in the middle of society. This is due to the lack of literacy from the general public. Important advocates need to be considered because in addition to providing legal advice by defending the rights of suspects in criminal and civil cases. In criminal cases, the client's interests are subjectively separated from the law, even though the suspect realizes that he made a mistake. Almost never heard of a voluntary criminal willing to be convicted. So the role of advocates in upholding economic law in Indonesia is really needed. Without the role of an advocate, law enforcement, especially those relating to economic law will not be enforced.